Vloga primarne socializacije pri oblikovanju ekoloških vrednot mladostnikov: kvalitativna raziskava med srednješolci - Omulec, Andrej (Anali PAZU HD, 2026)
The development of ecological values is a key process in fostering environmentally responsible behaviour, with primary socialisation playing a crucial role. This study examined how secondary school students perceive the influence of primary socialisation on the development of ecological values. A qualitative research approach was employed. Data were collected through a focus group involving eight purposively selected secondary school students and analysed using qualitative content analysis. The findings indicate that participants perceive the family as the most influential factor in the development of ecological values, emphasising parental role modelling, everyday family practices, and direct experiences. School is recognised as an important setting for developing environmental knowledge, while the media are viewed primarily as a source of information that reinforces existing environmental attitudes. Participants highlight that personal example, experiential learning, and everyday behaviour have a stronger influence than the mere transmission of information. The study provides a qualitative insight into secondary school students' understanding of ecological value formation and highlights the importance of primary socialisation as a foundation for sustainable behaviour.
Keywords: Dijaki; Družina; ecological values; ekološke vrednote; kvalitativna raziskava; primarna socializacija; primary socialization; qualitative research; Socializacija; Trajnostni razvoj